Generation of monthly flows in the Casma River basin up to the Tutuma Hydrometric Station using the GR2M precipitation-runoff model - Rojas Villegas, Jose Luis; Edson Nayger, Tomas Ayala; Carmona Arteaga, Abel (LACCEI, 2024)
The present work is carried out in the Casma basin up to the Tutuma Hydrometric Station, with the objective of generating the flows at a monthly rate for a period of 31 years using the GR2M model. The GEE platform was used to obtain the temperature (ERA5) and precipitation (RAIN4PE) data. Information was obtained from the Water Observatory on daily flows, which were averaged monthly, from the Tutuma Hydrometric Station between the period from October 1982 to September 1985, which was used for the calibration and validation of the model. The analysis of results was given taking into account the criteria of efficiency, the Nash coefficient and Determination R2